Penubuhan Sekolah Agama Swasta:Maahad Tahfiz Sains Yayasan Khairiah - Illiana Alia binti Zakaria; Illiana Aini binti Zakaria; Abd. Muhaimin bin Ahmad; Syed Najihuddin Syed Hassan (Academic Inspired Network, 2024)
Non-Indexed Publication